Analisis Kestabilan Lereng pada Lereng Akhir Penambangan PT. Koto Alam Sejahtera Kecamatan Pangkalan Koto Baru Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - ALVIN IRANTO PURNAMA; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Koto Alam Sejahtera is a private company engaged in the mining of andesite stone with open pit mining with quarry method. The mining activity forms a final slope whose stability is not yet known. In addition, the presence of weak areas on the final mining slope can weaken the rock mechanical parameters and there are fractures and water seepage on the slope which has a slope angle of 81 ° with a slope height of 12.343m. Therefore, it is necessary to have an analysis of the stability of the slopes at that location to prevent landslides. In this study, the analysis used was kinematic analysis with dips’s software and slope stability analysis using Morgenstern-Price method. Based on the results of kinematic analysis, the percentage value of potential landslides that occurred at the research location was the type landslide which had a landslide Flexural Toppling potential of 18,27%. Based on the analysis of the safety factor (FK) of the slope using Morgenstern-Price method, it shows that the final slope of mining is in a critical condition (FK <1.0) with a FK value of 0.894 in saturated conditions. Therefore, changes in slope geometry were made to obtain safe conditions (FK> 1.3) by reducing the slope angle from 81 ° to 60 ° so that the FK value was 1.326.Keywords: Quarry mining, kinematic analysis, Morgenstern-Price method, FK (safety factor)